Vision-Based Real-Time Indoor Positioning System for Multiple Vehicles⁎This research is supported by the Deutsche Forschungsgemeinschaft (DFG, German Research Foundation) within the Priority Program SPP 1835 "Cooperative Interacting Automobiles" and the Post Graduate Program GRK 1856 "Integrated Energy Supply Modules for Roadbound E-Mobility". Issue 2 (2020) - Kloock, Maximilian; Scheffe, Patrick; Tülleners, Isabelle; Maczijewski, Janis; Kowalewski, Stefan; Alrifaee, Bassam
Abstract: We propose a novel external indoor positioning system that computes the position and orientation of multiple model-scale vehicles. For this purpose, we use a camera mounted at a height of 3.3 m and LEDs attached to each vehicle. We reach an accuracy of about 1.1 cm for the position and around 0.6° for the orientation in the mean. Our system is real-time capable with a soft deadline of 20 ms. Moreover, it is robust against changing lighting conditions and reflections.